Asteroid Photometry And Lightcurve Results For Seven Asteroids - Colazo, Milagros Rita (2022)
Synodic rotation periods and lightcurve amplitudes are reported for: 308 Polyxo, 488 Kreusa, 494 Virtus, 570 Kythera, 702 Alauda, 877 Walkure, and 995 Sternberga.